EMOTION REGULATION THROUGH AUDIO JOURNAL: A CASE STUDY OF VISUALLY IMPAIRED PEOPLE IN SENTRA MAHATMIYA BALI: A Descriptive Study in the Social Work Intervention - Ningtias, Novi Saskia; Faisyahril, Ria; Rahmawati, Atik; Nufus, Belgis Hayyinatun; Mayangsari, Wahyuni; Choirotunnisa, Maisaroh (Politeknik Kesejahteraan Sosial Bandung, 2025)
Blind people are individuals who have limitations in their sense of sight which causes difficulties in responding to social situations, limitations or difficulties in carrying out activities so that assistance is needed from the role around blind people, namely families, people with disabilities have a more sensitive emotional side than other individuals, so the process of recognizing emotions and channeling emotions must be done early, emotional regulation plays a role in the psychological, emotional and health well-being of blind people with disabilities. Health has an influence on the psychology of people with disabilities because it intersects with the mental health of people with disabilities, so all elements of psychology, health, and social have a role in improving the functioning and well-being of the subject. Stable Psychic will affect the social functioning of the subject in the community environment, the process of interaction and social communication of the Family has a role in helping to regulate the emotions of blind people with disabilities so that they are more emotionally, psychologically, health and socially stable, The study aims to determine the process of regulating emotions, recognizing emotions, expressing emotions, and channeling emotions carried out by blind people with disabilities using audio jumaling. Audio jumaling was chosen because it is in accordance with the conditions of blind people with disabilities. The study used a qualitative method with a case study approach. Data collection was carried out using interview techniques, documentation and observation of (one) sub-vector through the assessment process, intervention planning and implementation of audio jumaling vaccine interventions. The results of the study found that sub-vectors had difficulty in regulating emotions due to internal and external problems such as family and friendship, emotions that were not channeled properly made the subject _ so that audio jumaling was needed as an effort to help the process of regulating the emotions of people with visual disabilities. Audio jumaling helps social workers at the Mahatmiva Center to be able to strengthen and provide optimal services.